Colorectal carcinoma: Importance of colonic environment for anti-cancer response and systemic immunity - Vannucci, Luca; Stepankova, Renata; Grobarova, Valeria; Kozakova, Hana; Rossmann, Pavel; Klimesova, Klara; Benson, Veronika; Sima, Petr; Fiserova, Anna; Tlaskalova-Hogenova, Helena (Journal of immunotoxicology, 2009)
The intestinal environment is considered to play an important role both in colorectal tumor development and in the evolution and modulation of mucosal immunity. Studies in animals reared in germ-free (GF, without any intestinal microflora) versus conventional (CV, with regular microflora in bowel) conditions can aid in clarifying the influence of bacteria on carcinogenesis and anti-cancer immune responses in situ. The lower incidence of colon cancers and better immunological parameters in GF animals versus CV ones after chemically-induced carcinogenesis raises questions about specific characteristics of the immunological networks in each respective condition. Different levels of tolerance/regulatory mechanisms in the GF versus CV animals may influence the development of immune responses not only at the level of mucosal, but also at the systemic, immunity. We hypothesize that GF animals can better recognize and respond to evolving neoplasias in the bowel as a consequence of their less-tolerogenic immunity (i.e., due to their more limited exposure to antigens to become tolerated against at the intestinal level). In this paper, we review the role of bacteria in modulating gut environment and mucosal immunity, their importance in cancer development, and aspects of immune regulation (both at local and systemic level) that can be modified by bacterial microflora. Lastly, the use of GF animals in comparison with conventionally-raised animals is proposed as a suitable and potent model for understanding the inflammatory network and its effect on cancer immunity especially during colorectal cancer development.
Keywords: Rats; Killer Cells, Natural; kolorektální nádory; imunologická tolerance; Immunity, Innate; slizniční imunita; Disease Models, Animal; Colorectal Neoplasms; Receptor Cross-Talk; adenokarcinom; Mice; gnotobiologické modely; krysa rodu Rattus; přirozená imunita; Colon; interakce mezi receptory a ligandy; modely nemocí na zvířatech; zvířata; Humans; kolon; Germ-Free Life; myši; Immune Tolerance; buňky NK; Immunity, Mucosal; Adenocarcinoma; lidé; Animals